2006
DOI: 10.4049/jimmunol.177.4.2651
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 Regulates Angiogenesis via Activation of Ets-1 Transcription Factor

Abstract: Although recent studies have suggested that CC chemokine CCL2 may directly affect the angiogenesis, the signaling events involved in such regulation remain to be determined. This study investigated a potential signal mechanism involved in CCL2-induced angiogenesis. Our in vitro and in vivo (hemangioma model of angiogenesis) experiments confirmed earlier findings that CCL2 can induce angiogenesis directly. Using a gene array analysis, CCL2 was found to induce expression of several angiogenic factors in brain en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
141
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 52 publications
(49 reference statements)
8
141
0
1
Order By: Relevance
“…The TFBS for members of the ETS family like ETS-1, ELF-1, and SPI1 which are involved in regulation of extracellular matrix (46), vascular development (47), and cellular migration (48), were also significantly overrepresented during endotoxin tolerance. These findings could also be connected to the substantial upregulation of MCP-1 (CCL-2) observed in our time-course experiments during endotoxin tolerance, as MCP-1 has been previously linked with the regulation of angiogenesis through activation of the ETS-1 transcription factor (49).…”
Section: Discussionmentioning
confidence: 58%
“…The TFBS for members of the ETS family like ETS-1, ELF-1, and SPI1 which are involved in regulation of extracellular matrix (46), vascular development (47), and cellular migration (48), were also significantly overrepresented during endotoxin tolerance. These findings could also be connected to the substantial upregulation of MCP-1 (CCL-2) observed in our time-course experiments during endotoxin tolerance, as MCP-1 has been previously linked with the regulation of angiogenesis through activation of the ETS-1 transcription factor (49).…”
Section: Discussionmentioning
confidence: 58%
“…38,39 However, it has been shown that CCL2 may also have a direct effect on angiogenesis. 40,41 Our current findings suggest that CCL2 expression is modulated by TF in ECs. Indeed, we found that endogenous TF can promote microvessel stabilization through CCL2 expression, promoting via HVSMC-CCR2 migration to the newly formed endothelial tubes, which agrees with the finding that CCL2 stimulates SMC migration.…”
Section: Discussionmentioning
confidence: 73%
“…In vivo, CCL2-mediated angiogenesis has been demonstrated in corneal implantation, chick chorioallantoic membrane, Matrigel plug, and sponge implantation models (33)(34)(35), and appears to be independent of its induction of leukocyte recruitment (34). The chemotaxis of endothelial cells by CCL2 is dependent on CCL2-induced over-expression of membrane type 1-metalloproteinase on endothelial cell surfaces (31) and is mediated via the ERK cascade and the transcription factor Ets-1 (36).…”
Section: Chemokinesmentioning
confidence: 99%